Evaluasi Keberhasilan Revegetasi Lahan Reklamasi Tambang Menggunakan Data Sentinel-2 dengan Metode NDVI dan Pengamatan Lapangan di PT. Bara Energi Lestari, Kabupaten Nagan Raya, Provinsi Aceh - Yoessi Oktarini; Rahman Hakim; Pocut Nurul Alam; Dewi Sartika; Yulianis (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Reclamation of former coal mining land is an obligation for mining companies to restore environmental conditions that have been disturbed due to mining activities. PT Bara Energi Lestari has carried reclamation and revegetation efforts in its former mining areas. The use of satellite imagery or remote sensing plays an important role in evaluating reclamation and revegetation activities. Satellite imagery greatly facilitates the evaluation process, particularly in analyzing land cover, improving time efficiency, and providing diverse visual data. Therefore, this study aims to evaluate the progress of revegetation in the reclamation areas of PT Bara Energi Lestari during the third reclamation period (2020–2024) and to assess the success of revegetation efforts through the analysis of the Normalized Difference Vegetation Index (NDVI). The study utilized NDVI data derived from Sentinel-2 imagery acquired from 2020 to 2024, which were spatially analyzed to examine changes in revegetation levels within the reclamation areas over the study period. The results of the analysis show that the revegetation efforts carried out in the reclamation areas of PT Bara Energi Lestari during the 2020–2024 period, which initially planned a reclamation area of 46.31 hectares, were ultimately realized on a reduced area of 43.91 hectares. Based on the analysis, the reclamation area from 2020 showed a vegetation cover of 98%, the 2021 area had 99%, the 2022 area had 89%, while the 2023 area dropped to 16%, and the 2024 area had only 9% vegetation cover.